On the Asymmetry for Convex Domains of Constant Width (Communications in Mathematical Research, 2021)
The extremal convex bodies of constant width for the Minkowski measureof asymmetry are discussed. A result, similar to that of H. Groemer's and of H. Lu's,is obtained, which states that, for the Minkowski measure of asymmetry, the mostasymmetric convex domains of constant width in $\boldsymbol{R}^2$ are Reuleaux triangles.